THE ROLE OF SOCIAL CAPITAL IN RAJUDIN SAGALA'S VICTORY IN THE 2024 MEDAN CITY LEGISLATIVE GENERAL ELECTION - Reza Putra Pratama; Muryanto Amin; Indra Kesuma Nasution (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aims to analyze the use of social capital by Rajudin Sagala from the Prosperous Justice Party in winning the 2024 Medan City Legislative General Election. Using Robert D. Putnam's social capital theory which includes networks, norms, and trust, as well as the typology of bonding social capital and bridging social capital, this study applies a descriptive qualitative approach. Data was collected through in-depth interviews, observations, and documentation of key informants (Rajudin Sagala), winning teams, and party elites. The results of the study show that in the aspect of bonding social capital, Rajudin Sagala strengthens internal solidarity through da'wah activities, mosque safaris, and PKS cadre training that instills the values of ukhuwah, loyalty, and trust. This activity creates a strong emotional bond with mosque worshippers and party cadres. Meanwhile, bridging social capital is realized through social assistance programs (basic necessities, compensation, education assistance) and free medical services that reach people across social groups, including ngaji teachers, funeral homes, and underprivileged families. The program builds public trust and broad moral legitimacy. In conclusion, the synergy between bonding and bridging social capital supported by consistency of presence and religious values was a key factor in Rajudin Sagala's victory with the highest number of votes obtained in Dapil I of Medan City.